ORE MINERALOGY AND MINERAL CHEMISTRY OF PYRITE, GALENA, AND SPHALERITE AT SORIPESA PROSPECT AREA, SUMBAWA ISLAND, INDONESIA - Win Kant; I Wayan Warmada; Arifudin Idrus; Lucas Donny Setijadji; Koichiro Watanabe (Geological Engineering Department Universitas Gadjah Mada, 2015)
The Soripesa prospect area is located at Maria village, Wawo district, Bima region in the East Sumbawa Island, Indonesia. Lithology is dominantly composed of a lithic-crystal tuff of andesitic and dacitic composition and bedded limestone. The polymetallic epithermal quartz veins are hosted by andesitic volcaniclastic rocks. Within these veins, multiphases, colloform-crustiform, bedding to massive textures with pyrite, sphalerite, galena, chalcopyrite, chalcocite, azurite, and malachite are observed. Selected samples were analyzed by using ore microscopy and SEM-EDX. Ore minerals show replacement, ex-solution, colloform, and zonal textures. The paragenesis diagram was made from a careful study of polished sections and thin sections. Textures of ore minerals such as banded, exsolution, replacement, and zone, have been interpreted to correspond to the order of deposition. In pyrite, the average content of Co (0.45 wt.%) is higher than Ni content (0.14 wt.%) and it means that their origin may be hydrothermal origin. Average content ratio, Co:Ni is 2.81. Galena shows a low Ag content of 0.07 %in average. But they show a high Au content of 1.48 %in average. Sphalerite shows a low Fe content of 1.04 %in average and occasionally chalcopyrite inclusion/disease also occurred. Ga and Ge contents are also high in sphalerite. Co>Ni in pyrite, low content of Ag in Galena, low content of Fe and mole % FeS in sphalerite, high content of Ga and Ge, and log (Ga/Ge) in sphalerite, show that pyrite, galena, and sphalerite from Soripesa prospect area were formed under low temperature condition of hydrothermal fluid. Keywords: Ore textures, paragenesis, deposition, hydrothermal fluid, low temperature